The complexity of VAT implementation on the supply of medicines in Indonesia: What are the consequences? - Wijaya, Farras Agung; Tambunan, Maria R.U.D. (WIM Solusi Prima, 2025)
The policy on the imposition of Value-Added Tax (VAT) on pharmaceutical transactions in Indonesia contributes to increasing state revenue. However, this policy has not yet fully favored the public, as VAT is one of the main factors in determining drug prices, which ultimately increases the financial burden on society, especially for those suffering from various illnesses.This study aims to analyze the VAT policy on pharmaceutical transactions and identify more effective policy alternatives. The research employs a qualitative approach, utilizing in-depth interviews and literature studies as data collection techniques. The findings indicate that this policy has not fully met the principle of ease in its administrative implementation. Therefore, the proposed policy alternatives include, firstly, classifying pharmaceutical products as essential goods exempt from VAT. Secondly, implementing a multi-tiered VAT system to reduce the tax burden on pharmaceutical transactions. This study recommends simplifying the tax mechanism to ensure easier implementation for taxpayers while also prioritizing the convenience of taxpayers in fulfilling their VAT obligations related to pharmaceutical transactions.